Sosialiasi Aplikasi Money Expense UMKM Pasar Lama Kota Tangerang - Almubarokah Tri; Yohana Beng; Aulia Muslim; Nila Safitry; Rencana Simbolon; Danu Tirta Mihardja (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2024)
Micro, Small and Medium Enterprises (UMKM) are a crucial element that reflects the development of prosperity in most developing countries. Considering the great potential of UMKM which is proven through their business activities which involve almost all sectors, and are spread throughout the country (Amirullah, 2002: 7). The existence of an application that aims to make it easier for UMKM to record their finances is important. This application can act as a tool for managing financial transaction records, including expenses and income, so that the processing results can produce profit/loss and cash flow reports in accordance with applicable accounting standards.